Identification of Milankovitch sedimentary cycle in Fengcheng Formation, Mahu depression: a case study of well Maye 1 - Wang, Ran; Chen, Xuan; Chang, Qiusheng; Zhao, Xinmei (Frontiers in Earth Science, 2024)
The sedimentary cycle of Fengcheng Formation in Junggar Basin changes rapidly and is difficult to identify. The low classification accuracy of high-frequency fine-grained sedimentary cycles restricts the exploration of unconventional shale oil and gas.Full-interval coring of well Maye 1 provides a solid foundation for small-layer research. This paper studies the high-frequency sedimentary cycles of the Milan Kovacevic in the Fengcheng Formation using techniques such as spectral analysis and wavelet transformation, and establishes a high-resolution astronomical age scale. The study reveals the control of orbital periodic changes on organic matter in mudstone, and based on this, identifies the sweet spots. Using the 405ka long-period eccentricity, 100ka short-period eccentricity, and 42736a long-period axial tilt as semi-quantitative criteria for the fourth, fifth, and sixth-order sequence division, the Fengcheng Formation is divided into two fourth-order sequence cycles, nine fifth-order sequence cycles, and 16 sixth-order sequence cycles. The application of the 405ka long-period eccentricity reveals two large-scale lake regression-transgression sedimentary cycles in the regional Fengcheng Formation, and a maximum lake flooding surface in the middle period of Feng II, corresponding to high organic matter abundance and great hydrocarbon generation potential. The application of the 100ka short-period eccentricity identifies eight sweet spot intervals in the Fengcheng Formation of Well Maye 1, which is consistent with the nuclear magnetic interpretation results. The research provides a semi-quantitative basis for the identification of high-frequency sedimentary cycles and sweet spot intervals in the Fengcheng Formation of the Mahu depression in the Junggar Basin, and provides a reference for the subsequent division of highfrequency fine-grained sedimentary cycles.